Enhanced acidogenic fermentation from Al-rich waste activated sludge by combining lysozyme and sodium citrate pretreatment: perspectives of Al stabilization and enzyme activity - Zhang, Pengfei (2023)
The accumulation of poly aluminum chloride (PAC) in dewatered waste activated sludge (WAS) can cause severe Al pollution and significantly reduce the production of volatile fatty acids (VFAs) from anaerobic fermentation. Herein, the combination of lysozyme and sodium citrate pretreatment was applied to stabilize the aluminum and enhance the VFAs production via anaerobic fermentation. The complexation and stabilization of aluminum by the citrate was efficient, which is conducive to relieving the inhibition of aluminum on lysozymes and other extracellular hydrolases. Compared with the control group, the lysozyme, protease and α-glucosidase activities were obtained at 1.86, 1.72, and 1.15 times, respectively, following the pretreatment. 129.71 mg/g volatile suspended solids (VSS) of soluble proteins and 26.3 mg/g VSS of polysaccharides were obtained within 4 h, together with the degradation of 124 % more proteins and 75 % more polysaccharides within three days. This provided a sufficient number of substrates for VFA production. 588.4 mg COD/g VSS of total VFAs were obtained after the six-day anaerobic fermentation from Al-rich WAS following the combination of lysozyme and sodium citrate pretreatment, which was 7.3 times higher than that of the control group. This study presents a novel approach for enhancing VFA production in anaerobic fermentation as well as reducing risk of Al hazards from Al-rich WAS.